Effects of attractiveness, image and satisfaction on word of mouth communication - Dyah Sugandini; Mohamad Irhas Effendi; Yenni Sri Utami; Agus Sasmito Aribowo (Universitas 'Aisyiyah Yogyakarta, 2020)
Travel activities have become the lifestyle of today's society. Many people take advantage of a holiday just to travel to various tourist attractions. In the context of tourism, lifestyles are also associated with activities, hobbies, opinions, which play an important role in consumer behavior. Trend tours that became a lifestyle one of them is special interest tourism. Dolandeso is one of the special interest attractions with environmental conservation mission based on cultural values and local wisdom. Dolandeso is a community-run tourism and is a Community based Tourism (CBT). Dolandeso tourism is a blend of the beauty of the environment, nature and value of harmonization between humans. This study aims to analyze the Word of Mouth (WOM) model influenced by satisfaction, image and attractiveness. This research uses 100 international tourist respondents. The sampling technique uses convience sampling. Data analysis using two step approach to SEM. The results show that the WOM model is acceptable. Satisfaction has positive effect on WOM, image has positive effect on attractiveness and satisfaction, attractiveness has positive effect on satisfaction.